Curriculum Evaluation on National Standard Pre-School of Islamic Education Component : Penilaian Kurikulum Standard Prasekolah Kebangsaan (Semakan 2017) Komponen Pendidikan Islam - Madar, Mohd Azahar; Othman, Mohd Syaubari (Jurnal Pendidikan Bitara UPSI, 2022)
The effectiveness of curriculum implementation can be seen when the curriculum developed is able to achieve the goals within the set period. In order to obtain information related to the implementation of the curriculum, the evaluation of the curriculum needs to be carried out holistically including various aspects. This coincides with the purpose of curriculum evaluation which is to determine whether the curriculum objectives have been implemented or achieved the desired results. There are several models that are often used to evaluate the curriculum. Each model has strengths and weaknesses. The decision to select a model to evaluate the curriculum is determined based on the purpose of the evaluation. Therefore, this concept paper aims to review the models related to curriculum evaluation and identify the appropriate model to evaluate the preschool curriculum component of Islamic Education. In the future, it is hoped that more studies related to preschool curriculum evaluation will be carried out to improve the preschool education curriculum in Malaysia.